Optimal Water Backwashing Condition in Combined Water Treatment of Alumina Microfiltration and PP Beads - Hyungmin Cho; Gihoon Yoon; Minjae Kim; Jin Yong Park (Membranes, 2022)
Membrane fouling is a dominant limit of the membrane separation process. In this research, the optimal water backwashing to solve the membrane fouling problem was investigated in the combined water treatment process of alumina MF and pure polypropylene (PP) beads. Additionally, the influence of membrane shape (tubular or seven channel) was examined, depending on the water backwashing period. The optimal backwashing time (BT) could be 20 s in the combined water treatment process, because of the highest total treated volume (VT) in our BT 6–30 s conditions. The optimal backwashing period (BP) could be 6 min, because of the minimum membrane fouling and the maximum VT in the combined process of tubular alumina MF and PP beads. The resistance of reversible membrane fouling (Rrf) showed a major resistance of total membrane fouling, and that of irreversible membrane fouling (Rif) was a minor one, in the combined process using tubular or seven channel MF. The Rif showed a decreasing trend obviously, as decreasing BT from NBW to 2 min for seven channel MF. It means that the more frequent water backwashing could be more effective to control the membrane fouling, especially irreversible fouling, for seven channel membranes than tubular membranes.